I have a PDF:

$$f_y(y) = \frac{\lambda^n}{\Gamma(n)} (y-n\tau)^{n-1}e^{-\lambda(y-n\tau)}$$

I want to find the moment generating function for it: (I believe I made a mistake somewhere?)

$$\begin{aligned} M(t) = E[e^{Yt}] &= \int_0^\infty e^{yt} \frac{\lambda^n}{\Gamma(n)} (y-n\tau)^{n-1}e^{-\lambda(y-n\tau)} \; dy \\ &= \frac{\lambda^n e^{\lambda n \tau}}{\Gamma(n)} \int_0^\infty e^{-y(\lambda-t)(y-n\tau)^{n-1} \; dy} \\ & \text{... let } u = y(\lambda-t) \\ &= \frac{\lambda^n e^{\lambda n \tau}}{\Gamma(n)} \int_0^\infty e^{-u} (\frac{u}{\lambda-t}-n\tau)^{n-1} \frac{1}{\lambda-t} \, du \end{aligned}$$

Usually after the substitution I would get something that I know how to integrate like a PDF of some distribution or in this case perhaps a gamma function? But in this case it looks complex? Maybe I made a wrong substitution?

Since the PDF is that of a gamma distribution, I expected the MGF of a gamma distribution which I belive should be $$\frac{\lambda}{\lambda-t}n$$ in this case?


Ok probably 1 of my mistakes is after changing variables, my limits of integration should change ... but I am not sure how to proceed after:

after change of variables

$$\begin{aligned} &= \frac{\lambda^n e^{\lambda n \tau}}{\Gamma(n)} \int_{n\tau (\lambda - t)}^\infty e^{-u} (\frac{u}{\lambda-t} - n\tau)^{n-1} \frac{1}{\lambda-t} \, du \\ &= \frac{\lambda^n e^{\lambda n \tau}}{\Gamma(n) (\lambda - t)^n} \int_{n\tau (\lambda - t)}^\infty e^{-u} (u-n\tau (\lambda-t))^{n-1} \, du \end{aligned}$$

The integral looks like a gamma function? But how do I handle $u-n\tau (\lambda-t)$? I got a feeling it have something to do with the limits of integration, but I am not sure what ...


You wanted to shift the gamma distribution, but you didn't shift it. Your integral should start from $n\tau$.

\begin{aligned} M(t) = \int_{n\tau}^\infty e^{yt} \frac{\lambda^n}{\Gamma(n)} (y-n\tau)^{n-1}e^{-\lambda(y-n\tau)} \; dy. \end{aligned} Now apply the change of variables $u = y-n\tau$ to get \begin{aligned} M(t) = e^{n\tau t}\int_{0}^\infty e^{ut} \frac{\lambda^n}{\Gamma(n)} u^{n-1}e^{-\lambda u} \; du. = e^{n\tau t}\times\mbox{MGF of unshifted Gamma}(t) \end{aligned} Meanwhile, we have also shown that the MGF of the shifted PDF is just $e^{t\,\mathtt{SHIFTAMOUNT}}$ times the unshifted MGF, and all this calculation was actually not necessary :)

  • $\begingroup$ Hmm, sorry but I am wondering even if I have $\int_{n\tau}^\infty$ how do I integrate that complex expression? $\endgroup$ – Jiew Meng Nov 6 '13 at 5:42
  • $\begingroup$ If you start from $n\tau$, it will be straightforward to integrate (after a change of variables) - You won't get that complicated integral. $\endgroup$ – Lord Soth Nov 6 '13 at 5:43
  • $\begingroup$ ok I updated the OP with what I have got after your help (many thanks btw!), but I am still alittle stuck ... $\endgroup$ – Jiew Meng Nov 6 '13 at 6:47
  • $\begingroup$ @JiewMeng Edited. $\endgroup$ – Lord Soth Nov 6 '13 at 7:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.